1962
DOI: 10.1146/annurev.pp.13.060162.002155
|View full text |Cite
|
Sign up to set email alerts
|

Longevity of Plant Organs: Internal Factors Controlling Abscission

Abstract: The research of many men during the last twenty years has gone toward elucidating the internal factors which control the longevity of two importan t types of plant organs-leaves and fruits. This work, which one would expect to have general interest for developmental biologists, has not been as familiar to them as it might be because most of the papers which could be considered to treat longevity have emphasized the "abscission" side of the research. The emphasis on abscission is quite understandable: there are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
34
0

Year Published

1964
1964
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 49 publications
2
34
0
Order By: Relevance
“…Prior to this discovery, it had been reported that the attachment of orchid (Dendrobium spp.) pollinia, known to be rich in auxin, to excised coleus tissue dramatically slowed abscission (Laibach, 1951) and that application of indoleacetic acid (IAA) to the distal end of bean (Phaseolus vulgaris) leaf explants delayed cell separation (Jacobs, 1962). These observations led to the hypothesis that the timing of shedding was regulated by the auxin-ethylene balance within the AZ tissues, with a high flux of IAA into these cells, from the subtending organ, preventing abscission from taking place (Taylor and Whitelaw, 2001).…”
mentioning
confidence: 99%
“…Prior to this discovery, it had been reported that the attachment of orchid (Dendrobium spp.) pollinia, known to be rich in auxin, to excised coleus tissue dramatically slowed abscission (Laibach, 1951) and that application of indoleacetic acid (IAA) to the distal end of bean (Phaseolus vulgaris) leaf explants delayed cell separation (Jacobs, 1962). These observations led to the hypothesis that the timing of shedding was regulated by the auxin-ethylene balance within the AZ tissues, with a high flux of IAA into these cells, from the subtending organ, preventing abscission from taking place (Taylor and Whitelaw, 2001).…”
mentioning
confidence: 99%
“…IAA is usually found in highest concentration in the juvenile parts of the plant, and at lower levels in regions removed from the growing points (10) and in the older leaves (4). In some cases, the senescence process may, in fact, be regulated by the changing levels of this hormone.…”
mentioning
confidence: 99%
“…Equally well documented (see "Reviews" 17,18,29,31,48) is the ability of auxin to retard or prevent abscission. The amount of auxin reaching the abscission zone and the distribution of auxin both proximal and distal to the abscission zone appear to play an important role in this preventive action of auxin (8,17,29,48).…”
mentioning
confidence: 99%